Answer:
See details below
Step-by-step explanation:
Your equation is [tex]x^{(4)}+17x''-17x'+17x=-9\cos(2t)[/tex]. Solve for the fourth derivative to get [tex]x^{(4)}=-17x''+17x'-17x-9\cos(2t)[/tex]
Now apply said change of variables: let [tex]x_1=x,x_2=x',x_3=x'',x_4=x^{(3)}[/tex]. Then, substituting on out first equation, we obtain the system:
[tex]x_4'=-17x_3+17x_2-17x_1-9\cos(2t)[/tex]
[tex]x_4=x_3'[/tex]
[tex]x_3=x_2'[/tex]
[tex]x_2=x_1'[/tex]
In general, if you have an nth order ordinary differential equation, you can apply the same idea to obtain a system of differential equations with n unknowns. Therefore, solving systems of differential equations is equivalent to solving higher-order differential equations.